Research progress of mosquito-borne virus mRNA vaccines - Ningze Sun; Zhiwei Su; Xiaoyan Zheng (Molecular Therapy: Methods & Clinical Development)
In recent years, mRNA vaccines have emerged as a leading technology for preventing infectious diseases due to their rapid development and high immunogenicity. These vaccines encode viral antigens, which are translated into antigenic proteins within host cells, inducing both humoral and cellular immune responses. This review systematically examines the progress in mRNA vaccine research for major mosquito-borne viruses, including dengue virus, Zika virus, Japanese encephalitis virus, Chikungunya virus, yellow fever virus, Rift Valley fever virus, and Venezuelan equine encephalitis virus. Enhancements in mRNA vaccine design, such as improvements to the 5′ cap structure, 5′UTR, open reading frame, 3′UTR, and polyadenylation tail, have significantly increased mRNA stability and translation efficiency. Additionally, the use of lipid nanoparticles and polymer nanoparticles has greatly improved the delivery efficiency of mRNA vaccines. Currently, mRNA vaccines against mosquito-borne viruses are under development and clinical trials, showing promising protective effects. Future research should continue to optimize vaccine design and delivery systems to achieve broad-spectrum and long-lasting protection against various mosquito-borne virus infections.